The Place of Enucleation and Enucleo-Resection in the Treatment of Pancreatic Metastasis of Renal Cell Carcinoma - Yazbek, Thierry; Gayet, Brice (JOP. Journal of the Pancreas, 2012)
Context Renal cell carcinoma has shown less response to systemic therapies including chemotherapy, radiotherapy and immunotherapy than other cancers. Metastasis of renal cell carcinoma to the pancreas occurs, even after long term radical nephrectomy, surgical resection remains the only potentially curative intervention. We performed surgery for pancreatic metastatic renal cell carcinoma and analyzed the results. Methods We retrospectively analyzed 11 patients who had undergone pancreatic resection or metastasectomy at our hospital from January 1994 to January 2010. Patient’s demographics, clinical variables, types of pancreatic resections (standard or atypical resection), primary histopathology, surgical outcomes, survival and disease free interval were examined. We compared the standard pancreatic resection to atypical resection (enucleation or enucleo-resection). Results Eleven patients underwent 14 pancreatic resections or metastasectomy (3 pancreaticoduodenectomy, 4 distal pancreatectomy, 1 completion of pancreatectomy, 4 enucleations and two enucleo-resections) for pancreatic renal cell carcinoma metastasis. The median age was 73 years, the median time period between nephrectomy and finding of pancreatic metastasis was 11.4 years. One patient showed synchronous pancreatic metastatic lesions on radiology. One patient died from a splenic artery pseudoaneurysm rupture 35 days after the surgery. Major complications occurred in 4 patients with standard resection (one hemoperitoneum, three pancreatic fistulas), and in one patient with atypical resection (duodenal fistula); six patients with standard resection presented postoperative diabetes mellitus. Median survival age was 6.5 years (range 1-9 years). Two patients died of metastatic disease 5 to 6 years, while 7 patients are alive and well 1 to 9 years after surgery. Conclusions According to these results and regardless of the small number of cases, atypical resection of metastatic renal cell carcinoma has a high median survival rate even after pancreatic recurrence or distant metastasis. It seems reasonable to favor a good quality of life and less diabetes with a limited atypical resection. Image: Institut Mutualiste Montsouris. Paris, France.